2022
DOI: 10.1111/mice.12892
|View full text |Cite
|
Sign up to set email alerts
|

Systemic reliability of bridge networks with mobile sensing‐based model updating for postevent transportation decisions

Abstract: This paper proposes the upscaling of conventional individual bridge health monitoring problems into urban regions and transportation networks via mobile and smart sensing techniques together with an innovative reconnaissance procedure. The paper associates structural failure probabilities with systemic features and proposes decision criteria to optimize postdisaster actions. Twenty bridges constituting transportation network infrastructure compose the testbed region and utilize smartphone accelerometers for dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 123 publications
0
9
0
Order By: Relevance
“…Apart from multiple techniques integrated into each other, different studies merged multiple smartphone camera data for an enhanced deformation monitoring experience [ 39 , 40 ]. Complexity was not limited to the alternative physical meaning of different sensor technologies but also the scale of the SHM problem, e.g., bridge populations [ 41 ], bridge networks, and high-level analytics, such as decision-making [ 42 ]. Figure 1 presents the timeline of these key progresses in smartphone-based SHM.…”
Section: Smartphone Technology and Bridge Shmmentioning
confidence: 99%
See 3 more Smart Citations
“…Apart from multiple techniques integrated into each other, different studies merged multiple smartphone camera data for an enhanced deformation monitoring experience [ 39 , 40 ]. Complexity was not limited to the alternative physical meaning of different sensor technologies but also the scale of the SHM problem, e.g., bridge populations [ 41 ], bridge networks, and high-level analytics, such as decision-making [ 42 ]. Figure 1 presents the timeline of these key progresses in smartphone-based SHM.…”
Section: Smartphone Technology and Bridge Shmmentioning
confidence: 99%
“…The authors expanded the smartphone clock problem into a probabilistic description and identified a Kernel distribution formulation to represent the smartphone sampling rate imperfections [ 60 ]. At the same time, the authors linked modal identification findings to calibrate bridge finite element models [ 42 ]. Stemming from the benchmark works developed for a seismic shake table test [ 61 , 62 ], the authors interpreted smartphone-based bridge SHM as a cyber-physical process and utilized model updating for structural reliability supporting decision-making [ 63 ].…”
Section: Invasive Smartphone Sensing For Bridge Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, to represent the actual fragility curves, a detailed analysis is required. However, initial steps to achieve this was made in a parallel research study by the authors in [68].…”
mentioning
confidence: 99%